Role of endometrial blood flow assessment with color Doppler energy in predicting pregnancy outcome of IVF-ET cycles - Lina Wang; Jie Qiao; Rong Li; Xiumei Zhen; Zhaohui Liu (2010)
Abstract This is a prospective study of 182 women (38 yrs or younger) undergoing IVF-ET. Endometrial thickness, echo pattern and blood flow on transvaginal ultrasonography were recorded eight hours prior to hCG administration. The patients were divided into three groups: A (n = 10) with undetectable endometrial blood flow; B (n = 82) with sub-endometrial blood flow; C (n = 90) with both endometrial and sub-endometrial blood flow. According to IVF-ET outcomes, all patients were re-divided into three groups: 1 non-pregnancy (n = 92); 2 intrauterine pregnancy with live fetus (n = 70); 3 others (n = 20 including biochemical pregnancy, embryonic diapause, ectopic pregnancy and miscarriage). Intrauterine pregnancy with live fetus in Group C (62.2%) was much higher than that in Group A and B (0% and 17.1%, p less than or equal to 0.001). The implantation rate (33.2%) was much higher than that in Group A and B (0% and 19.90%, p less than or equal to 0.001). The pulsatility index, resistance index, and S/D of endometrial spiral arteries were 0.1 +/- 0.2, 0.6 +/- 0.1 and 2.5 +/- 0.4 in Group 2, which were much lower than those in Group 1 and Group 3 (p1-2 less than 0.001, p2-3 less than 0.05). The patients with detectable endometrial blood flow had higher clinical pregnancy rates and implantation rates.